Intensi remaja pergi ke kafe susu di Sleman DIY - Hilma Farhani; Susetyowaty Susetyowaty; Atik Triratnawati (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Intention of teenager in consuming milk at milk cafe of Sleman YogyakartaPurposeThis study aimed to explore the intentions of adolescents who come into the cafe milk in Sleman.MethodsThis study used a qualitative method with an exploratory and phenomenological design, with purposive sampling by considering the prescribed criteria. Informants of this study were thirteen informants. They consisted of nine adolescents, one manager of the cafe, two employees cafe and one academic nutritionist. Data collection was done from March-May 2015 by observation and interviews.ResultsResults showed that intention of adolescents who come to the cafe were for refreshments, using the facilities such as wifi (coursework), and for an organization's activities (meetings). Adolescent attitudes were positive and support the cafe milk and milk consumption behavior. Subjective norms included among others that adolescents wanted to socialize, to be recognized, to share information and build closer relationships with their friends.ConclusionThe health aspect is not the main intention of adolescents to come to the cafe milk. Adolescents come to the cafe milk with different intentions. Adolescents consume the milk in milk cafe because it has many benefits. However, the health benefits were only the last intention. The consumer intention was influenced by the positive attitudes of adolescents towards the cafe milk which includes media promotion of health and the subjective norm of adolescents toward the consumption of milk in the milk cafe.